The m6A Reader YTHDF1 Facilitates the Tumorigenesis and Metastasis of Gastric Cancer via USP14 Translation in an m6A-Dependent Manner - Chen, Xiao-Yu; Liang, Rui; Yi, You-Cai; Fan, Hui-Ning; Chen, Ming; Zhang, Jing; Zhu, Jin-Shui (Frontiers in Cell and Developmental Biology, 2021)
Abstract Objectives: N6-methyladenosine (m6A) RNA methylation is implicated in the progression of multiple cancers via influencing mRNA modification. YTHDF1 can act as an oncogene in gastric cancer (GC), while the biological mechanisms via which YTHDF1 regulates gastric tumorigenesis through m6A modification remains largely unknown. Methods: GEO and TCGA cohorts were analyzed for differentially-expressed m6A modification components in GC clinical specimens and their association with clinical prognosis. Transwell and flow cytometry assays as well as subcutaneous xenograft and lung metastasis models were used to evaluate the phenotype of YTHDF1 in GC. Intersection of RNA/MeRIP-seq, luciferase assay, RIP-PCR, RNA pull-down and MeRIP-PCR were used to identify YTHDF1- modified USP14 and its m6A levels in GC cells. Results: High-expressed YTHDF1 was found in GC tissues and was related to poor prognosis, acting as an independent prognostic factor of poor survival in GC patients. YTHDF1 deficiency inhibited cell proliferation and invasion (in vitro), and gastric tumorigenesis and lung metastasis (in vivo) and also induced cell apoptosis. Intersection assays revealed that YTHDF1 promoted USP14 protein translation in an m6A-dependent manner. USP14 up-regulation was positively correlated with YTHDF1 expression and indicated a poor prognosis in GC. Conclusions: Our data suggested that m6A reader YTHDF1 facilitated tumorigenesis and metastasis of GC by promoting USP14 protein translation in an m6A-dependent manner and might provide a potential target for GC treatment.